An aboriginal community-controlled health organization model of service delivery: qualitative process evaluation of the Tulku wan Wininn mobile clinic - H. Beks; F. Mitchell; J.A. Charles; K.P. McNamara; V.L. Versace (International Journal for Equity in Health, 2022)
Abstract Background Mobile clinics have been implemented in diverse clinical and geographical settings to provide proximal health care for specific populations. Primary health care mobile clinics have been implemented widely for Indigenous populations, with a paucity of research evaluations around service delivery models internationally. To redress factors impeding service accessibility for Aboriginal and Torres Strait Islander Peoples, Budja Budja Aboriginal Cooperative (Aboriginal Community Controlled Health Organisation located in a small rural town in Victoria, Australia), developed and implemented the Tulku wan Wininn primary health mobile clinic. Methods A qualitative process evaluation methodology was used to explore contextual factors mediating the implementation of the mobile clinic, including the acceptability of the service to health service personnel, external key informants, and Aboriginal and/or Torres Strait Islander clients. A synthesis of international ethical guidelines, (Consolidated Criteria for strengthening reporting of health research involving Indigenous peoples (CONSIDER statement), was prospectively applied to shape the study design and research process. Semi-structured interviews were conducted with participants. Data collection occurred from July 2019 to October 2021. Inductive thematic data analysis was undertaken concurrently with data collection. Results Data was collected from 19 participants which included 12 health service personnel and key informants, and 7 Aboriginal clients. In total, data from 22 interviews were included as interviews with three clients were undertaken twice. Four themes were developed: considerations for early implementation, maintaining face-to-face services during COVID-19, acceptability as a model of service delivery, and maintaining the mobile clinic as a service delivery model. Conclusion Evidence supporting the acceptability of a primary health care mobile clinic for Aboriginal Peoples residing in rural Victoria is provided. Despite the experience of early implementation challenges and adaptations, the mobile clinic addressed known transport and cultural barriers to accessing primary health care services. In the context of COVID-19 lockdowns, the mobile clinic was valued for the provision of face-to-face care for Aboriginal clients. Key issues for maintaining the mobile clinic include health workforce and funding. Findings are of value to other organizations seeking to implement a primary health mobile clinic service delivery model to redress barriers to accessibility experienced by the communities they serve.